DEDALUS’ GRIN. ANDRZEJ KIJOWSKI’S CONFRONTATIONS WITH PARIS - Kopczyk, Michał (Porównania, 2019)
Michał Kopczyk, DEDALUS’ GRIN. ANDRZEJ KIJOWSKI’S CONFRONTATIONS WITH PARIS. “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 147-162. ISSN 1733-165X. The article offers a reading of Andrzej Kijowski’s works which constitute a record of the writer’s stay in the capital of France – the essay Sezon w Paryżu [A Season in Paris] and fragments of his diary. The author of the article focuses especially on the intellectual aspect of these experiences, reconstructs the political diagnoses of the author-protagonist, analyses his perception of the relationship between his native culture and that of Western Europe (especially of France), and the condition of both at the time. The intellectual dimension of the texts is closely bound with their personal dimension, as can be seen for example in the way that A Season in Paris praises culture – and the human being – as particularly “non-aseptic” phenomena, resisting rationalization. The intellectual ferment in which the visitor found France, engrossed in the “Algerian war,” became in this perspective an equivalent of the reevaluations provoked in the writer by his journey. The author of the article points to the similarities between the writer’s diagnoses and those formulated today within the framework of postcolonial research on Central-Eastern Europe.